A Comparative Study of Job Satisfaction and Attitude towards Education among Male and Female Teachers - Roy, Dr. Mamta (The journal of contemporary issues in business and government, 2019)
The purpose of this study was to discover and compare the attitudes of job-satisfied and job-dissatisfied female instructors regarding teaching. An initial sample of 1000 female elementary school teachers who had worked in their department for more than five years was taken from four districts in Kashmir valley. The final sample was obtained after the original sample was subjected to the Quartile Deviation (Q3) and Q1 techniques. UmmeKulsum’s "Attitude towards Teaching Profession Scale(ASTTP)" and Meera Dixit’s "Job Satisfaction Scale for Teacher (JSST)" were employed by the researchers. The data was statistically treated appropriately, with Mean, Standard Deviation (SD), and a test of significance ("t"-test) being used. The findings demonstrated that Job Satisfied and Dissatisfied women instructors differed considerably in their attitudes toward teaching, with Job Satisfied women teachers having a better attitude toward teaching than Job Dissatisfied women teachers.